Leptin is required for hypothalamic regulation of miRNAs targeting POMC 3′UTR - Derghal, Adel; Djelloul, Mehdi; Airault, Coraline; Pierre, Clément; Dallaporta, Michel; Troadec, Jean-Denis; Tillement, Vanessa; Tardivel, Catherine; Bariohay, Bruno; Trouslard, Jérôme; Mounien, Lourdes (Frontiers in Cellular Neuroscience, 2015)
The central nervous system (CNS) monitors modifications in metabolic parameters or hormone levels and elicits adaptive responses such as food intake regulation. Particularly, within the hypothalamus, leptin modulates the activity of pro-opiomelanocortin (POMC) neurons which are critical regulators of energy balance. Consistent with a pivotal role of the melanocortin system in the control of energy homeostasis, disruption of the POMC gene causes hyperphagia and obesity. MicroRNAs (miRNAs) are short noncoding RNA molecules that post-transcriptionally repress the expression of genes by binding to 3′-untranslated regions (3′UTR) of the target mRNAs. However, little is known regarding the role of miRNAs that target POMC 3′UTR in the central control energy homeostasis. Particularly, their interaction with the leptin signaling pathway remain unclear. First, we used common prediction programs to search for potential miRNAs target sites on 3′UTR of POMC mRNA. This screening identified a set of conserved miRNAs seed sequences for mir-383, mir-384-3p, and mir-488. We observed that mir-383, mir-384-3p, and mir-488 are up-regulated in the hypothalamus of leptin deficient ob/ob mice. In accordance with these observations, we also showed that mir-383, mir-384-3p, and mir-488 were increased in db/db mice that exhibit a non-functional leptin receptor. The intraperitoneal injection of leptin down-regulated the expression of these miRNAs of interest in the hypothalamus of ob/ob mice showing the involvement of leptin in the expression of mir-383, mir-384-3p, and mir-488. Finally, the evaluation of responsivity to intracerebroventricular administration of leptin exhibited that a chronic treatment with leptin decreased mir-488 expression in hypothalamus of C57BL/6 mice. In summary, these results suggest that leptin modulates the expression of miRNAs that target POMC mRNA in hypothalamus.